PENGEMBANGAN MEDIA VISUAL FLYER BERBASIS CANVA TERHADAP MOTIVASI BELAJAR SISWA KELAS IX SMP AL-TAMIMI - Herawati, Desi; Rukanda, Nandang; Novianti, Williya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research was conducted because of problems in student motivation experienced by SMP Al-Tamimi students, resulting in students finding it difficult to focus on subjects or enthusiasm for learning. Therefore, students need to have learning motivation to increase their learning motivation. The subjects in this study were 10 class 1X students of SMP Al-Tamimi who had difficulty focusing on learning or increasing their enthusiasm for learning. The method that researchers use is the Research and Development (R&D) method. As for data collection in this study using a questionnaire which is calculated by the percentage description formula. The validation process was carried out with experts, namely media experts, materials and practitioners. After going through the media flyer validation process it is very feasible to be tested with an average score of 67% for media experts, 60% for material experts and 71% for practitioner experts. Questionnaire instrument for data collection as many as 28 items of learning motivation questionnaire statements. based on the results of research on class 1X students of SMP Al-Tamimi before receiving media flyer guidance services in the low category with a percentage score of 39%. And the site that has been given services with media flyers increases with a percentage score of 70% so that it can be categorized as very high. As for the results of the limited scale test with 10 subjects getting an average score of 70% in the very high category and the results of the wide scale test or sample of 33 people getting an average score of 83% in the very high category.